Anthrosols and ancient agriculture at Sanyangzhuang, Henan Province, China. (June 2018) - Storozum, Michael J.; Qin, Zhen; Liu, Haiwang; Fu, Kui; Kidder, Tristram R.
Abstract: Although soils are classically considered to be formed through a variety of geological and biological processes, an increasing amount of evidence suggests that human activity also played a significant role in soil formation in antiquity. By identifying anthropogenic additions into ancient soils, archaeologists can understand many of the social and geological processes that formed ancient landscapes. We present geoarchaeological research from the Sanyangzhuang site, Henan Province, China, to examine how this area's long history of agricultural production altered soils from the Neolithic to the Iron Age. We use soil micromorphology and geochemistry to study the anthropogenic residues left behind in ancient soils and compare our results with the historical and archaeological records. Our results suggest that the transition from wooden to iron tools at the beginning of the Iron Age played an important role in the long-term formation of ancient agricultural soils at Sanyangzhuang, and by extension, in much of ancient China. Highlights: Presents micromorphological and geochemical evidence showing human influence on soil forming conditions at Sanyangzhuang Changes in geochemistry and structure of soil relate to economic shifts in ancient Chinese society Studying anthropogenic soilscapes can reveal how social and technological change have altered the environment